2000
DOI: 10.1346/ccmn.2000.0480402
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermal Stability of Al-Pillared Smectites Modified with Ce and La

Abstract: Abstract--A commercial bentonite (primarily smectite) from Fischer Scientific Company (F bentonite) and a natural bentonite from Peru (P bentonite) were used in the preparation of pillared clays with potyoxymetal cations of A1 that were subsequently modified with Ce and La. Several Al/metal ratios (5 and 9) were used to investigate the effects on the thermal and hydrothermal stability of these synthetic clays. The structure of these materials was studied by X-ray diffraction. Isotherms were determined by N2 ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
20
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 40 publications
(47 reference statements)
1
20
0
1
Order By: Relevance
“…The basal spacings reported by Valverde et al (2000) are in a similar range to those reported by others for Al-pillared smectites (Kloprogge, 1998 and references therein), but -6--7 A smaller than those reported for the A1 and rare-earth element (A1/REE) large-pore pillared smectites (McCauley, 1988; Sterte, 1991a Sterte, , 1991bBooij et al, 1996aBooij et al, , 1996b. This indicates that rare earth elements do not form an integral part of the pillars within the interlayer.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…The basal spacings reported by Valverde et al (2000) are in a similar range to those reported by others for Al-pillared smectites (Kloprogge, 1998 and references therein), but -6--7 A smaller than those reported for the A1 and rare-earth element (A1/REE) large-pore pillared smectites (McCauley, 1988; Sterte, 1991a Sterte, , 1991bBooij et al, 1996aBooij et al, , 1996b. This indicates that rare earth elements do not form an integral part of the pillars within the interlayer.…”
mentioning
confidence: 96%
“…Unfortunately, Valverde and coworkers (Valverde et aL, 2000) missed most of the important publications on the thermally stable large-pore pillared clays based on AI pillars modified by Ce or La. The basal spacings reported by Valverde et al (2000) are in a similar range to those reported by others for Al-pillared smectites (Kloprogge, 1998 and references therein), but -6--7 A smaller than those reported for the A1 and rare-earth element (A1/REE) large-pore pillared smectites (McCauley, 1988;Sterte, 1991aSterte, , 1991bBooij et al, 1996aBooij et al, , 1996b.…”
mentioning
confidence: 98%
See 3 more Smart Citations